MOTIVASI PETANI DALAM BUDIDAYA TANAMAN CABAI DI DESA RAANAN BARU KECAMATAN MOTOLING BARAT KABUPATEN MINAHASA SELATAN - Dolfina ., Krois; Ribka M. Kumaat; Theodora M Katiandagho (Sam Ratulangi University, 2021)
This study aims to determine the motivation of farmers in chili cultivation and the factors that influence the motivation of farmers in cultivating chili plants in Raanan Baru Village. The data analysis used in this research is descriptive analysis using the Likert scale. This research was conducted for three months, from January to March 2020. The research took place in Raanan Baru Village, Motoling Barat District, South Minahasa Regency. The data used in this study are primary data and secondary data. Primary data obtained through interviews with 30 farmers who cultivate chili plants as research samples. Secondary data were obtained from the village office, the Motoling Barat sub-district office, South Minahasa district The results showed that the motivation of farmers in cultivating chili plants in Raanan Baru Village was found that sociological motivation had a high interpretation value of 443.3 percent in the hope that it could fulfill their economic needs. Sociological motivation arose because of the desire to strengthen harmony and exchange opinions among chili farmers. Economic motivation has a high value interpretation with a percentage of 464 percent. Economic motivation arises because of the desire to get a higher income which can have a positive impact.Â